A BRIEF HISTORY OF UNDROP AND CHALLENGES TO ITS IMPLEMENTATION IN INDONESIA - fadillah Kaban, afgan; Harahap, Handra (Talenta Publisher, 2022)
The Indonesian government has issued agrarian reform policies to improve peasants' access to their means of production, particularly land, and reduce land inequality. Agrarian reform is carried out with asset legalization, land redistribution and social forestry. One of the things that may be highlighted is the struggle to encourage the implementation of UNDROP has not been fully supported by social movements in Indonesia in large numbers. The formulation of UNDROP does not occur at one particular moment, but through a process of discussion that takes place for several years before the finalization stage and is brought to the international space. This conference was a moment for UNDROP where it endorsed UNDROP as an international struggle of LVC and produced the Declaration on the Rights of Peasant – Women and Men. When the food crisis occurred, the LVC explained before the United Nations that the adoption of the UN Convention on the Rights of peasants could be the basis for solutions to discrimination against peasants and the food crisis. In the context of policy, the Government of Indonesia still tends to focus on policies that encourage economic growth through the withdrawal of investment and free trade.